Realisme Magis dalam Rondontō Karya Natsume Soseki - Laily Raff Firdausy; Syahrur Marta Dwisusilo (Jentera: Jurnal Kajian Sastra, 2023)
It is said that magical realism first appeared in Germany in the 1920s. However, this also allegedly contained in Natsume Soseki’s Rondontō (published in 1905), way before the concept itself was being established. Rondontō tells about the visit of Japanese student to the Tower of London, where he experienced various irrational things. To prove Rondontō's values as a text with the genre of magical realism, we use five categorizations of magical realism by Wendy B. Faris. with literature review method. We categorize the magical realism characteristic in this text where irreducible elements were found in the form of the presence of spirits, then phenomenal world elements were fouind through the detailed descriptions and the appearance of unusual elements themselfs. In addition, there is also an element of unsettling doubt that is raised through the doubts of the main character in understanding his experience, which is connected to the merging of realms where the two worlds are joined between the fantasy stage and the real world. The main character keeps moving in time and places which indicates the occurrence of space and time disturbances. The presence of these five categorizations of magical realism indicates that Rondontō contains magical realism in it. Therefore, the statement that the concept of magical realism first appeared in Germany in the 1920s can not be said to be fit, but rather focuses only on its development in the west.